Features of the functioning of glutonic names in a female novel by Larisa Denisenko “Cinnamon coffee taste” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article deals with the process of studying of glutonic names that represent the features of the glutonic discourse which there is an object of interest of scholars not only from the point of view of linguistics and its individual areas, such as: linguoculture, linguistics, linguistic and semiotics, but also cultural studies, sociology and literary studies.The article investigates the multi-aspect phenomenon of glutonium, reveals the meaning of the concept of “glutonium”, outlines the structural-semantic and lingvo-cultural features of the glutonic names represented in the novel by Larisa Denisenko “Cinnamon coffee taste”. The peculiarities of the functioning of the nuclear and peripheral zone of glutoniums were established, it was found that one-component and multi-component names differ in their composition and origin, and in the basis of differential motivational features. The main types of multicomponent nomines are identified and described, most of which are two-component noun-adjective phrases.The results of the investigation showed that glutoniums are one of the leading and prominent themes of national linguistics, since they represent the so-called “eatable panorama” of artistic Ukrainian literature of the XXI century, whose texts are not yet sufficiently studied from the point of view of glutonic discourse.
Keywords: glutonic discourse; glutonium; glutonia; names of dishes